2004
DOI: 10.1088/0022-3727/37/21/010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the absolute CF2concentration in a dielectric barrier discharge running in argon/fluorocarbon mixtures

Abstract: The role of different CFx-radicals in plasma polymerization in fluorocarbon mixtures has not been determined yet. Therefore spectroscopic investigations of dielectric barrier discharges (DBDs) in argon/fluorocarbon mixtures at atmospheric pressure were conducted with the focus on measurement of the concentration of CFx-radicals. The following diagnostic procedures were applied: FTIR absorption spectroscopy to diagnose stable compounds in the discharge, optical emission spectroscopy of the DBD in the UV and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Compared to filament discharges at atmospheric pressure, the low-pressure glow-like discharges contribute to the deposition of FC films with very smooth surfaces. Vinogradov et al found dusty-like particles with their sizes in the range of 0.1-1 μm for FC films deposited at atmospheric pressure [17,18]. Dusty-like particles can be produced due to strong filament discharges at atmospheric pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to filament discharges at atmospheric pressure, the low-pressure glow-like discharges contribute to the deposition of FC films with very smooth surfaces. Vinogradov et al found dusty-like particles with their sizes in the range of 0.1-1 μm for FC films deposited at atmospheric pressure [17,18]. Dusty-like particles can be produced due to strong filament discharges at atmospheric pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The gas spacing between the electrodes can be varied in the range of 0.1 mm to several mm. DBDs have been used to deposit fluorocarbon films at atmospheric pressure [17,18]. However, plenty of dust-like particles on the surface have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Vinogradov et al [40,41] investigated the deposition of fluorocarbon films in filamentary DBDs fed with different fluorocarbons, e.g. CF 4 , C 2 F 6 , C 2 H 2 F 4 , C 3 F 8 , C 3 HF 7 and c-C 4 F 8 , in mixture with Ar; an in situ investigation of the plasma phase was performed by means of UV absorption spectroscopy, Fourier transform infrared (FT-IR) absorption spectroscopy, and optical emission spectroscopy.…”
Section: Atmospheric Pressure Pe-cvd Of Fluorocarbon Thin Filmsmentioning
confidence: 99%
“…Analysis of the intensity ratios between SPS and CH(A), and between FNS and CH(A), has instead shown that CH(A) excitation is not achieved by electron impact on CH but by dissociative excitation of CH 4 . In particular, in N 2 -CH 4 and in He-CH 4 , respectively: e + CH 4 → CH(A) + products (9) He(2 3 S) + CH 4 → CH(A) + products (10) Summing up the whole of these experiences, we conclude that the mixed discharge/post-discharge regime of a DBD, and the generally low average electron density, results in emission spectra that are far from being dominated by electron impact on the corresponding ground state. The relationship between the emission and the corresponding radical is then not at all straightforward, and sometimes even nonexistent.…”
Section: Herman Infrared System (Hir) This Emission Nmentioning
confidence: 99%
“…Non-emitting species measurement must be achieved by other techniques. Classical absorption (nontime-resolved) was applied to the detection of NO, NO 2 , NO 3 , N 2 O 5 , and O 3 in [8] and of CF 2 in [9], and two-photon LIF to the measurement of oxygen atoms in [10] and nitrogen atoms in [11]. We have explored this realm, touching many of the issues described above by a multidiagnostic approach with time-resolved optical diagnostics, applied to common DBD devices.…”
Section: Introductionmentioning
confidence: 99%